The Role of Job Satisfaction in Moderating the Influence of Intrinsic Motivation, Work Environment and Transformational Leadership on Teacher Performance (Universitas Negeri Semarang, 2022)
Teacher performance is influenced by various factors, this study aims to analyze teacher performance which is mediated by job satisfaction at SMK Negeri Pekalongan Regency. The study population was teachers at SMK Negeri Pekalongan district, 398 teachers in total. The sample of the study was 160 teachers spread over four State Vocational Schools in Pekalongan district. Data was collected through a questionnaire, which has been tested for validity and reliability. Data were analyzed by requirements analysis test, descriptive statistics, path analysis and Sobel test. The results showed: (1) the influence of work motivation on job satisfaction was 5.02%. (2) the influence of the work environment on job satisfaction is 2.79 % (3) the influence of the principal's leadership on job satisfaction is 27.55% (4 ) the influence of work motivation on teacher performance in total is 48.48%,; (5) the influence of the work environment on teacher performance is a total of 15.50%; (6) the principal's leadership on teacher performance is a total of 19.0%, (6) the influence of educational leadership on teacher performance is a total of 27.55%, (7) the influence of job satisfaction on teacher performance is 25.30% while the influence is positive and significant. It is recommended that teachers able to create and improve more conducive work environment, the Principal in leading expected to empower teachers and maintain two-way communication; for related agencies expected to make policies that are related to improving teacher performance.